Taxonomic review of the Dichotomius (Luederwaldtinia) assifer (Eschscholtz) species-group (Coleoptera: Scarabaeidae) - Nunes, Rafael V.; Carvalho, Marcela S. G.; Vaz-De-Mello, Fernando Z. (Zootaxa, 2016)
The Dichotomius assifer species-group, a component of Dichotomius (Luederwaldtinia) is taxonomically revised. The group now contains five species: D. angeloi sp. nov. (Holotype male deposited in CEMT: BRAZIL, Minas Gerais State, Vargem Bonita, Parque Nacional Serra da Canastra. Mata de Galeria, 28º18’39”S, 46º31’30”W. 865 m a.s.l., 02.XI.2011, MF Souza leg.), and D. louzadai sp. nov. (Holotype male deposited in CEMT: BRAZIL, Minas Gerais State, Lima Duarte, Parque Estadual Ibitipoca, VI.2001, FZ Vaz-de-Mello leg.) are described; D. assifer and D. affinis are redescribed and lectotypes are designated. D. machadoi is diagnosed. Illustrations, distributional records, diagnosis and a key for identification of the species in the group are provided. Some aspects of the natural history and biogeography of species in the assifer group are also discussed.